Elizabeth Bowen : theory, thought and things - Gildersleeve, Jessica; Smith, Patricia Juliana (Edinburgh University Press, 2019)
From experiments in language and identity to innovations in the novel, the short story and life narratives, the contributors discuss the way in which Bowen's work straddles, informs and defies the existing definitions of modernist and postmodernist literature which dominate twentieth-century writing.